Assessing and managing urban riverscapes: integrating physical processes and social-ecological values - Murphy, Brian Michael, author; Nelson, Peter, advisor; Wohl, Ellen, committee member; Grigg, Neil, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2022)
In the age of the Anthropocene, human influence has spread far and wide across our planet affecting the physical, chemical, and biological condition of the rivers, streams, and floodplains in the urban environment, our "urban riverscapes." The human connection to urban riverscapes includes both the built environment created and accessed by people and the intangible community values that humans place upon flowing water. The value of these benefits encourages stewardship of our waterways by integrating experiential, aesthetic, and cultural attributes that foster appreciation for streams as natural systems in the built environment. However, when poorly managed, human activities adversely impact our natural ecosystems, resulting in less resilient stream systems, poor aesthetics, and unsafe conditions. The research presented in this dissertation asks the following overarching research question: How can managers and practitioners apply multi-scale social-ecological, hydrologic, geomorphologic, and riparian ecological remote sensing and field data to advance urban riverscape management? Four chapters follow from this hypothesis: urban riverscape problems lie on a spectrum of complexity where solutions are often conceivable but difficult to implement. Integrating diverse perspectives and knowledge extends the scope of stakeholder perspectives so that social-ecological context is considered alongside the physical processes that typically characterize riverscapes. This approach entails leveraging existing and new methods to create frameworks that integrate the multi-scale assessment of physical conditions and social-ecological qualities underlying applied riverscape management. I explore the integration of diverse knowledge to enhance management outcomes through the concept of "wicked problems." I analyze the connections between diverse types of knowledge and practices through numerous case studies. My analysis shows how systematically characterizing project attributes, such as the prominence of local government and technical knowledge or the weakness of academia and indigenous knowledge, requires an approach that builds capacity and collaboration within transdisciplinary stakeholder groups. I find that the importance of integrating communities, including under-represented knowledge bases, into urban riverscape management can generate equitable and incremental solutions. To evaluate connections between social values, ecological conditions, and hydrogeomorphic processes, I outline a framework for urban riverscape assessment that advances the practice of managing urban riverscapes facing complex problems. The framework is based upon evaluation across four foundational categories, or facets, critical to the management of urban riverscapes: (1) human connections and values, (2) hydrologic processes and hydraulic characteristics, (3) geomorphic forms and processes, and (4) ecological structure and processes. I structure the framework around three tiers of actionable steps, which tackle the questions: Why are we assessing this riverscape (Tier 1)? What do we need to understand in and along this riverscape (Tier 2)? How will we assess the riverscape to develop that understanding (Tier 3)? I find that the answer to the first question is context-based and dependent upon integrating diverse types of knowledge, while the response to the second question involves examining the functions and values of urban riverscapes through the lens of the four facets and their inter-related processes. Answering the third question requires developing and testing a novel assessment method – the "Urban Riverscape conditions-Based Assessment for management Needs" (URBAN). I base URBAN on riverscape context and on integrating the assessment of facets at multiple scales. I apply the method to a test data set of publicly available and site-specific data across a study area in the Denver metropolitan region to illustrate its overall performance, including its ability to evaluate specific riverscape physical conditions and social-ecological qualities. I find reach typologies combined with urban riverscape characteristics provide tangible management strategies that managers can use to inform planning and decision making. The overarching conclusion of this dissertation is that managing urban riverscapes requires assessment methods that consider scale (spatial, temporal, and topical) and context (both physical and social characteristics), and the use of indicators and metrics that directly support decision-making among interdisciplinary stakeholders. It is possible to move toward this vision by using remote-sensed and field data that provides both social and physical information, to assess the relationship between physical condition and social-ecological values, and to use that information to determine where and how to prioritize management strategies for urban riverscapes.
Keywords: management strategies; reach typing; urban riverscapes; physical conditions; assessment; social-ecological values